Edukasi 6 Tahapan Mencuci Tangan dengan Media Kartu Bergambar Bagi Siswa Tk Pertiwi Singodutan II - Undari Nurkalis (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
The behavior of washing hands with soap is one of the pillars on which community empowerment is carried off as an approach to changing hygienic and sanitary behavior. Early childhood has the potential to support healthy life changes. Picture card media was used to convey messages and attract children's attention. Through these activities, it is hoped that students will be able to apply the six stages of proper hand washing and understand the importance of washing hands after doing outdoor activities, after finishing using the bathroom, and before consuming food. The method is carried off through an extension approach by providing education to Pertiwi Singodutan II Kindergarten students followed by a post-test and practice of the six stages of hand washing. The results obtained an average for the knowledge variable 95.65 and for the average hand washing practice variable was 93.46. The use of media images as an educational tool is effective in increasing students' knowledge about the correct steps for washing hands.